A new species of the genus Larnaca from Guangxi, China (Orthoptera: Gryllacrididae: Gryllacridinae) - Shen, Si-Zhong; Yin, Zi-Xu (Zootaxa, 2022)
Larnaca (Larnaca) lieyongzhou sp. nov. is described from Guangxi, China. This species is characterized by the unique shape of the lobes on female’s 7th abdominal tergite. Types of the new species in this paper are deposited in Museum of Biology, East China Normal University.